THE MEANING OF CONFLICT MEDIATION AFTER 15 YEARS OF LUIS ALBERTO WARAT'S ABSENCE AND 15 YEARS OF CNJ RESOLUTION 125 (ESMAT Magazine, 2025)
At the same time, 2010 marked the beginning of the National JudicialPolicy for the Adequate Treatment of Conflicts in Brazil, formalized by CNJ Resolution125. In the same period, Luis Alberto Warat died, a central figure in the theory of law inLatin America, whose work was fundamental to the development of legal education andstricto sensu postgraduate studies in law in the country. Both the regulations issued andWarat's reflections recognize mediation as a legal instrument capable of dealingadequately with conflicts. In light of this, this study seeks to analyze the introduction ofmediation in Brazil after the publication of CNJ Resolution 125, contrasting it with theWaratian perspective on the meanings of this institute. Based on this analysis, theresearch asks: is the structuring promoted by CNJ Resolution 125 to implementmediation in the Brazilian legal system in line with or different from Luiz AlbertoWarat's proposal? To answer this question, the hypothetical-deductive method will beadopted, with a qualitative analysis of specialized bibliography. The results show thatthe National Judicial Policy for the Adequate Treatment of Conflicts, established byCNJ Resolution 125, has been organized from a proceduralist perspective, unlike thesubstantialist approach advocated by Warat.
Keywords: CNJ Resolution nº 125; Luis Alberto Warat; Mediation; Proceduralism; Substantialism